Ethnic Identity and Political Participation Among Nigeria’s Ageing Population - Agunbiade, Doyinsola; Adumashi, Funke Abolade (Advances in Social Sciences Research Journal, 2026)
Nigeria’s demographic transition toward a growing ageing population presents new governance and equity challenges, particularly within the context of entrenched ethnic identities and political exclusion. This paper examines how ethnic identity shapes the political participation, representation, and civic engagement of older adults in Nigeria’s multicultural and politically fragmented landscape. Drawing on secondary data from scholarly articles, policy reports, demographic statistics, and empirical studies on ageing and identity politics, the paper explores the intersection between ethnicity, ageing, and democratic participation. Using Identity Politics Theory as the analytical framework, the study interrogates how ethnic belonging influences political behaviour, access to decision-making structures, and perceptions of political relevance among elderly citizens. It further assesses how longstanding ethnic inequalities, patronage dynamics, and regional disparities continue to affect older adults’ access to political platforms, voting behaviour, and institutional trust. The analysis highlights the implications of these dynamics for democratic consolidation, social cohesion, and equitable governance in Nigeria. The paper argues that understanding the experiences of ageing populations through the lens of ethnic identity is crucial for designing inclusive political processes and strengthening democratic participation. Findings from this study will contribute to emerging discourse on ageing, governance, and identity in Africa, offering insights for policymakers seeking to promote equitable representation.